Pertimbangan Hakim Dalam Memberikan Izin Poligami Terhadap Suami Yang Melakukan Perzinahan dalam Putusan Pengadilan Agama Tanjung Karang Nomor: 737/Pdt.G/2024/PA.Tnk - Siti Rani Dania; Kasmawati Kasmawati; Elly Nurlaili; Nunung Rodliyah; Sayyidah Sekar Kulsum (Pusat Riset dan Inovasi Nasional, 2026)
This study discusses the judge’s considerations in granting permission for polygamy to a husband who had committed adultery, as stated in the Religious Court Decision of Tanjung Karang Number: 737/Pdt.G/2024/PA.Tnk. Generally, Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 on Marriage upholds the principle of monogamy but allows polygamy under certain conditions with court approval. This case is particularly interesting because the court granted permission for polygamy to a husband who was proven to have engaged in an affair and committed adultery resulting in a child born out of wedlock. The study aims to identify the legal considerations of the judge and the legal implications regarding the marriage and joint property. The research employs an applied normative legal method with a qualitative approach, using primary data from interviews and secondary data from legislation and legal literature. The results show that the judge considered granting permission for polygamy as a means of legalizing the existing relationship to maintain public morality and prevent continuous sinful behavior, although it conflicts with moral values. Legally, the second wife has no rights over the joint property acquired before the polygamous marriage, as stipulated in Article 65 paragraph (1) letter b of the Marriage Law